Enhancing innovation performance through business process innovation: The strategic role of external collaboration - Gun Jea Yu; Joonkyum Lee; Bumsoo Kim (Global Business & Finance Review (GBFR), 2024)
Purpose: This research examines the effects of collaboration with external firms on innovation performance, with a specific focus on the mediating influence of business process innovation. The objective is to explore how external collaborations contribute to improving innovation performance by facilitating internal process innovations, enabling firms to effectively convert external knowledge into practical innovation results. Design/methodology/approach: Utilizing data from the Korean Innovation Survey (KIS), this research utilizes lo-gistic regression analysis to test the hypotheses concerning the relationships between external collaboration, business process innovation, and innovation performance. It measures innovation performance associated with product in-novation and assesses collaboration with external firms via a survey. Findings: The results demonstrate that external collaborations enhance innovation performance, emphasizing the value of external knowledge and the pivotal role of business process innovation in transforming this knowledge into tangible outcomes. This highlights the critical need to refine internal processes to maximize the benefits of external partnerships. Research limitations/implications: This study is limited by its focus on small and medium-sized enterprises in South Korea's manufacturing sector, so it may not fully represent the dynamics in other countries or sectors. Future research should explore the influence of external knowledge on firm performance across diverse contexts. Originality/value: This research contributes to the existing literature by highlighting the pivotal role of business process innovation as a key mediator in integrating external collaboration into firms' innovation strategies. By pro-viding empirical insights into the innovation practices of South Korean firms, it enriches the global discourse on innovation management. This study's integration of open innovation, firm attributes, and business process innovation into a unified analysis offers a comprehensive perspective on the factors influencing innovation success and under-scores the importance of internal processes in maximizing the benefits of collaboration with external firms.
Keywords: 650; Collaboration with external firms; Innovation performance; Process innovation; Mediation effect